Informationen Deutsch als Fremdsprache (De Gruyter, 2017)
Informationen Deutsch als Fremdsprache (Information on German as a Foreign Language) is one of the leading journals for teachers and scholars of German as a Foreign Language and is edited by the Fachverband Deutsch als Fremd- und Zweitsprache (FaDaF) and the Deutscher Akademischer Austauschdienst (DAAD). In times of migration and globalization Info DaF is an indispensible source of information for teachers of German throughout the world.